Thyroid Papillary Carcinoma in a Patient with Hyperthyroidism: A Case Report and Review of Literature - Zaid O. Malaibari; Maram T. Al Khatieb; Aesha M.A. Albrahemi Al-Johani; Abdulrahman A. Meccawy (Journal of King Abdulaziz University: Medical Sciences, 2023)
Thyroid carcinoma in hyperfunctioning thyroid is a rare entity and a rare clinical condition, but should be suspected as there is rising trend in these cases. While subtotal thyroidectomy is an adequate treatment for incidental small focus of malignancy, hyperfunctioning thyroid malignancy requires more aggressive treatment. This report presents a case of 41-year-old hyperthyroid man who was found to have papillary thyroid cancer with hyperplastic goiter; consistent with toxic goiter based on postoperative histopathology. This case shows the importance of proper evaluation of the thyroid to exclude malignancies even in hyperfunctioning thyroid patients. Thyroid cancer should be considered in the differential diagnosis of hyperthyroid goiter and Graves disease despite the rare association between them. Careful history and physical examination should be carried out. Although hot nodules in iodine or technetium scan may suggest a benign condition, malignancy should be always ruled out with histopathology examination.